Albumin coated trimethyl chitosan-based targeting delivery platform for photothermal/chemo-synergistic cancer therapy. (1st August 2020) - Hu, Haiyan; Qi, Qi; Dong, Ziyi; Yu, Xianglong; Mo, Yujia; Luo, Juyuan; Wang, Yan; Du, Shouying; Lu, Yang
Highlights: Multifunctional trimethyl chitosan/human serum albumin nanosystems were generated. IR780 and bufalin were loaded into polysaccharide nanoplatforms via ionic gelation. IR780-loaded nanoplatform generated a highly photothermal effect upon irradiation. Tumor distribution was enhanced by human serum albumin interaction. Nanoplatforms displayed superior synergistic tumor therapy. Abstract: Current metastatic breast cancer therapies are not only affected by limited drug delivery options, but also restricted to the monotherapies. Here, we synthesized trimethyl chitosan (TMC), loaded it with photosensitizer IR780 or bufalin by ionic gelation, and coated it with human serum albumin (HSA) by electrostatic absorption (designated TIH or TBH, respectively). The near-spherical nanoparticles had a size of approximately 30 nm, exerted strong photothermal effects, and enhanced cellular mitochondrion colocation and phototoxicity. Tumor microenvironments were disrupted by TIH-mediated photothermal effects, which enhanced the accumulation of a second TBH dose in the tumor that promoted deep penetration in the whole tumor mass. After laser irradiation our nanoplatform enhanced cancer tissue accessibility and substantially suppressed tumor growth, and causing a 98.46 % inhibition of lung metastasis. Thus HSA-masked TMC represents a promising tumor-targeted drug delivery strategy with synergistic modality that may improve the therapeutic outcome of metastatic breast cancer.